Draft Revised Code of Good Practices on Fiscal Transparency. (Policy Papers; Policy Paper, 2006)
The IMF is in the process of revising its 2001 Code of Good Practices on Fiscal Transparency. The four core principles of the original Code remain unchanged in the revision: institutional clarity, open budget processes, public information and integrity. However, the document has been updated and broadened to reflect recent developments and practices. The IMF is requesting public comment on the proposed revised Code. The deadline for comments is November 17, 2006.